Role of Visual Acuity & Contrast Sensitivity in Early Diagnosis of Cognitive Impairment in Parkinson’s Disease - R, Akash; Reddy, Chiramana Supreeth; Ramakrishnan, Abinaya (International Journal of Membrane Science and Technology, 2023)
The study aims to evaluate the role of visual acuity and contrast sensitivity in early diagnosis of cognitive impairment in Parkinson’s disease. This cross sectional study was performed us- ing validated assessments on cognitive function using Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). Visual acuity was assessed using LogMAR and contrast sensitivity using the Pelli-Robson test. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). One hundred patients presenting to the Neurology department for complaints satisfying the criteria for Parkinson’s disease at Saveetha Medical College and Hospital were randomly selected. The visual acuity and contrast sensitivity was found to be decreased in patients with low MMSE and MoCA scores, suggestive of visual function being a marker for progression of cognitive impairment in Parkinson’s disease. This could thereby be used in early diagnosis of dementia and in for- mulating a customised treatment plan for each individual. Parkinson’s disease has a deleteri- ous effect on various aspects of a person’s life, not just the motor functions. This in turn harms the day to day activities of the individuals, mainly the older age group and results in psychological disorders, like anxiety and depression. Therefore, this study aims to establish visual function as a marker for cognitive impairment in Parkinson’s disease, with the hopes of improving the quality of life of patients with this disease, thus revamping their purpose and outlook of their lives.